Predict-Observe-Explain Tasks in Chemistry Laboratory: Pre-Service Elementary Teachers' Understanding and Attitudes - Ayfer Mutlu; Burçin Acar Şeşen (Sakarya University, 2016)
This study was conducted to investigate the effects of laboratory activities based on predict-observe-explain tasks related to the subjects of "Mixtures, Physical and Chemical Changes, Acids and Bases" on pre-service elementary teachers' understanding and attitude toward chemistry lesson and chemistry laboratory. For this purpose, the pre-service elementary teachers were randomly assigned to experimental (N=26) and control (N=30) groups. The experimental group was instructed using laboratory activities based on predict-observe-explain task and the control group was taught using traditional cook-book design laboratory activities during ten weeks. For the data collection, a two-tier concept test, attitude toward chemistry lesson scale and attitude toward chemistry laboratory scale were applied before and after the instructions. The results indicated that the pre-service elementary teachers who were trained using laboratory activities based on predict-observe-explain task had significantly higher scores in terms of achievement and attitude toward chemistry lesson and laboratory than those taught by the traditional approach. It was also found that instruction for laboratory activities based on predict-observe-explain task was more successful in remediation of the predetermined alternative conceptions.